On the security of golden cryptosystems - Tahghighi, Muhammad; Turaev, Sherzod; Jaafar, Azmi; Mahmod, Ramlan; Said, M. Md. (Hikari Ltd, 2012)
In this paper we have investigated the security of different variants the golden cryptography, and showed that all the variants of the cryptosystem are not secure against chosen-plaintext attack.